ECONOMIC INJUSTICE IN THE NIGER DELTA, NIGERIA: LEGAL PRINCIPLE TO AID THE WEAK IN AN ADUMBRATED FEDERATION - Williams Ehizuwa Orukpe (Romanian Journal of Historical Studies)
Nigeria’s federalism is adumbrated. It is not consistent with the legal principle of quicquid plantatur solo solo cedit on which true federalisms are anchored. Under true federalism, states own and control the resources on top and underneath their land and make monthly allocation to the federal government. But in an adumbrated federation the reverse is the case. Hence, this paper examined how this problem is affecting the Niger Delta region of Nigeria; and the legal principle that can aid the weak people. It adopted the historical research methodology to achieve these objectives. It finds that in concord with the principle of quicquid plantatur solo solo cedit, in pre-colonial Niger Delta, “He who owned the land owned the resources found on top and underneath the land.” But under colonial rule, British need for raw material for the development of its metropolis paved the way for the distortion of the historical precedent of land tenureship and resource ownership in the Niger Delta. When crude oil was discovered in the region in 1956, the colonial government through series of Oil Ordinances commandeered and exploited it to the exclusion of the people. And at independence in 1960, the Nigerian Federal government followed suite. It continued this economic injustice through Land and Oil and Gas Laws that disregard the principle of quicquid plantatur solo solo cedit. Therefore, this paper concludes that sustainable peace-building in the Niger Delta is tied to the repositioning of Nigeria’s Land and Oil and Gas Laws than all else